2022
DOI: 10.1155/2022/9042345
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Dermal Papilla Cells Mediate Hair Follicle Stem Cell Proliferation through the Wnt3a/β-Catenin Signaling Pathway

Abstract: Both hair follicle stem cells (HFSC) and dermal papilla cells (DPC) are essential for hair follicle growth and proliferation. In this study, HFSCs and DPCs that made signature proteins like KRT14, KRT15, KRT19, α-SMA, and Versican were obtained. Cell coculture systems between HFSCs and DPCs were used to measure the increased PCNA protein content in HFSCs. Additionally, exosomes from dermal papilla cells (DPC-Exos), the overexpression and silencing of Wnt3a, could regulate the Wnt/β-catenin signaling pathway do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“… 13 This result corroborated findings of previous in vivo studies demonstrating hair growth effects including the acceleration of the telogen‐to‐anagen transition in mice, potentially through the upregulation of fibroblast growth factor and β‐catenin pathways 7,13,20 . DPCs may function as a paracrine regulator of hair follicle stem cells (HFSCs) and ORSCs 7,13–15 . Interestingly, another in vitro study showed that exosomes isolated from human ORSCs exhibited similar effects vice versa in DPCs (Table 1).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“… 13 This result corroborated findings of previous in vivo studies demonstrating hair growth effects including the acceleration of the telogen‐to‐anagen transition in mice, potentially through the upregulation of fibroblast growth factor and β‐catenin pathways 7,13,20 . DPCs may function as a paracrine regulator of hair follicle stem cells (HFSCs) and ORSCs 7,13–15 . Interestingly, another in vitro study showed that exosomes isolated from human ORSCs exhibited similar effects vice versa in DPCs (Table 1).…”
Section: Resultssupporting
confidence: 87%
“…7,13,20 DPCs may function as a paracrine regulator of hair follicle stem cells (HFSCs) and ORSCs. 7,[13][14][15] Interestingly, another in vitro study showed that exosomes isolated from human ORSCs exhibited similar effects vice versa in DPCs (Table 1). 17 Other potential sources of exosomes include myeloid-derived suppressor cells and amniotic fluid stem cells (Table 1).…”
Section: Preclinical Evidencementioning
confidence: 97%
“…DPCs and HFSCs were isolated as previously described [ 53 ]. DPCs were cultured in Mesenchymal Stem Cell Medium (ScienCell, SanDiego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…These studies provide the basis for the future use of artificial HFSCs and their exosomes for wound treatment. Additionally, dermal papilla cells-derived exosomes have been shown to promote hair follicle growth 80 - 82 . Although these studies did not clearly state that this exosome promotes wound repair, it can be speculated that it may also have a cooperative function in promoting skin cell regeneration.…”
Section: Introductionmentioning
confidence: 99%